2015
DOI: 10.1002/pi.4965
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis route to regioselectively functionalized bifunctional polyarene

Abstract: We report the regioselective oxidative synthesis of polyaminonaphthol sulfonic acid (PANSA) particles and firstly obtained nanoparticles with molecular weight of ca 23 200 g mol−1 using a template‐free polymerization process in which NaOCl was used as an oxidant in aqueous basic medium. Nanoparticles were characterized using NMR, Fourier transform infrared and UV‐visible spectroscopies, gel permeation chromatography, thermogravimetry (TG), differential scanning calorimetry (DSC), cyclic voltammetry, photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…PANSA was prepared by the oxidative polymerization of the ANSA as given in the literature [6]. Then, PANSA's blends with LDPE (supplied from İzmir Aliağa refinery, sample code:F00556) in 3 different mixing ratios were prepared with the help of a micro extruder and the characterization of the prepared blends was presented in the previous study ( Figure 1 In this study, virgine LDPE, 0.5, 1 and 3% PANSA doped LDPE were coded as AP 0, AP 0.5 , AP 1 and AP 3 , respectively.…”
Section: Materials 211 the Preparation Of Pansa And Pansa-ldpe Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…PANSA was prepared by the oxidative polymerization of the ANSA as given in the literature [6]. Then, PANSA's blends with LDPE (supplied from İzmir Aliağa refinery, sample code:F00556) in 3 different mixing ratios were prepared with the help of a micro extruder and the characterization of the prepared blends was presented in the previous study ( Figure 1 In this study, virgine LDPE, 0.5, 1 and 3% PANSA doped LDPE were coded as AP 0, AP 0.5 , AP 1 and AP 3 , respectively.…”
Section: Materials 211 the Preparation Of Pansa And Pansa-ldpe Blendsmentioning
confidence: 99%
“…In our previous study, we reported the synthesis and characterization of a conjugated phenolic polymer (PANSA) [6]. We prepared blends of this functional polymer with low density polyethylene (PANSA /polyethylene) [7] and the prepared blends were characterized by their physical and chemical aspects.…”
Section: Introductionmentioning
confidence: 99%